First principles what America's founders learned from the Greeks and Romans and how that shaped our country - Ricks, Thomas E. 1955- (Harper, an imprint of HarperCollins Publishers, 2020)
Examines how the educations of America's first four presidents, and in particular their scholarly devotion to ancient Greek and Roman classics, informed the beliefs and ideals that shaped the nation's constitution and government